Assessing Nutritional Balance and Its Influence on Physical Activity and Performance Among University Sports Students - ASLI, Hocine; BELKADI, Adel; BENNAMA, Nouria; DJOURDEM, Bendhiba (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Purpose: This study analyzes the nutritional balance both quantitative and qualitative of meals provided at university dining halls in Oran and explores how this balance relates to the physical activity levels of students at the Institute of Physical Education and Sports. Method: The research involved 134 male students (ages 18-25 years, body weight: 71.84±4.55 kg, height: 174.66±8.52 cm) living in university dormitories “S2,” “S5,” and “S1.” Food portions were measured, and students’ energy expenditure from physical activity was calculated, following energy value standards set by Gandy, Madden, and Holdsworth (2012). Results: The students’ average daily energy intake was 2729.93 kcal, while their energy expenditure from physical activity averaged 3277.66 kcal. According to Joan Webster’s 2020 guidelines, the recommended energy intake is 3521.6 kcal. The study revealed that energy intake was below recommended levels and energy expenditure was higher, suggesting a need for dietary adjustments to meet energy requirements due to high physical activity levels. Conclusion: There is a notable gap between energy intake and expenditure, influenced by poor meal planning rather than economic constraints. This imbalance may adversely affect physical performance and cognitive functions. A balanced diet that meets nutritional standards is crucial for optimizing both learning and physical performance. Article history: Received 2025 March 05; Revised 2025 April 12; Accepted 2025 April 22. Available online 2025.03.30; Available print 2025.05.30